Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1073/pnas.92.2.452
|View full text |Cite
|
Sign up to set email alerts
|

A relationship between protein stability and protein function.

Abstract: Enzymes are thought to use their ordered structures to facilitate catalysis. A corollary of this theory suggests that enzyme residues involved in function are not optimized for stability. We tested this hypothesis by mutating functionally important residues in the active site of T4 lysozyme. Six mutations at two catalytic residues, Glu-11 and Asp-20, abolished or reduced enzymatic activity but increased thermal stability by 0.7-1.7 kcal mol-1. Nine mutations at two substrate-binding residues, Ser-117 and Asn-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
461
2
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 654 publications
(511 citation statements)
references
References 39 publications
40
461
2
1
Order By: Relevance
“…Shoichet et al [38], examining the structure and function of T4 lysozyme, concluded that catalytic residues within the enzyme were not optimized for protein stability and that this was a general property of enzyme active sites. Enzyme active sites, therefore, are more susceptible to unfolding than the rest of the protein molecule due to the increased flexibility required for catalytic function.…”
Section: Discussionmentioning
confidence: 99%
“…Shoichet et al [38], examining the structure and function of T4 lysozyme, concluded that catalytic residues within the enzyme were not optimized for protein stability and that this was a general property of enzyme active sites. Enzyme active sites, therefore, are more susceptible to unfolding than the rest of the protein molecule due to the increased flexibility required for catalytic function.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to co-operativity, the binding-affinity differences could be attributed to the interactions between the catalytic domain of Hin and the DNA. The possibility that Hin residues 43 and 69 are solely involved in catalysis of the DNA inversion reaction, and that inhibition of this reaction stabilizes DNA recognition and binding (Shoichet et al, 1995), cannot be ruled out. Studies with the EcoRV restriction endonuclease suggest that DNAcleavage ability can be linked to DNA binding (Vipond and Halford, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Too much stability would mean not enough flexibility for effective catalysis, whereas too little stability means too short a useful lifetime [7]. Point mutations which increase enzyme stability often lower specific activity [44,[67][68][69], and vice versa. There is, therefore, strong evidence for the contention that enzyme stability, flexibility and activity are closely interrelated, and that a balance between stabilizing and destabilizing interactions is required to meet the conflicting demands of stability on the one hand, and catalytic function and cellular turnover on the other.…”
Section: Inter-relationship Of Enzyme Stability and Activitymentioning
confidence: 99%